2022
DOI: 10.1101/2022.10.28.513298
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Engineered vasculature induces functional maturation of pluripotent stem cell-derived islet organoids

Abstract: Blood vessels play a critical role in pancreatic islet health and function, yet current culture methods to generate islet organoids from human pluripotent stem cells (SC-islets) lack a vascular component. Here, we engineered 3D vascularized SC-islet organoids by assembling SC-islet cells, human primary endothelial cells (ECs) and fibroblasts both in a non-perfused model and a microfluidic device with perfused vessels. Vasculature improved stimulus-dependent Ca2+ influx into SC-β-cells, a hallmark of β-cell fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…Protocol A was derived from our previously published protocol (Xu et al, 2011), with modifications in the late stages of differentiation based on (Rezania et al, 2014) and (Pagliuca et al, 2014). Protocol B was further modified using Stages 1-4 from Nostro et al (2015) to derive an improved pancreas progenitor population, and with factors such as BayK 8644 and MK-801 added to the end stages influenced by (Zhu et al, 2016)and (Huang et al, 2017). Although SC-islets from both protocols, Protocol A and Protocol B, have relatively low glucoseresponsive function, we find that major gene expression differences between these two protocols warrant the use of these SC-islets for further study.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Protocol A was derived from our previously published protocol (Xu et al, 2011), with modifications in the late stages of differentiation based on (Rezania et al, 2014) and (Pagliuca et al, 2014). Protocol B was further modified using Stages 1-4 from Nostro et al (2015) to derive an improved pancreas progenitor population, and with factors such as BayK 8644 and MK-801 added to the end stages influenced by (Zhu et al, 2016)and (Huang et al, 2017). Although SC-islets from both protocols, Protocol A and Protocol B, have relatively low glucoseresponsive function, we find that major gene expression differences between these two protocols warrant the use of these SC-islets for further study.…”
Section: Resultsmentioning
confidence: 99%
“…Once SC-islets are transplanted into a suitable environment, they experience myriad interactions and signals that are absent in vitro , including vascularization, frequent stimulation by feeding cycles, circadian entrainment, contact with the in vivo microenvironment including ECM-signaling and cell-cell interactions with endothelial, mural, neuronal, and immune cells. The effects that some of these individual elements have on islet and SC-islet health and function have been explored in vitro through many different studies, and each have been shown to have influence on the identity and function of the cells ( Alvarez-Dominguez et al, 2020 ; Singh et al, 2020 ; Nguyen-Ngoc et al, 2022 ; Tremmel et al, 2022 ). Together, it is possible that these elements of the tissue microenvironment provide combined cues to stimulate the final push towards maturation that cells require.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations